Enhancing the diversity of breeding invertebrates within field margins of intensively managed grassland: Effects of alternative management practices. Issue 22 (19th October 2017) - Fritch, Rochelle A.; Sheridan, Helen; Finn, John A.; McCormack, Stephen; Ó hUallacháin, Daire
Abstract: Severe declines in biodiversity have been well documented for many taxonomic groups due to intensification of agricultural practices. Establishment and appropriate management of arable field margins can improve the diversity and abundance of invertebrate groups; however, there is much less research on field margins within grassland systems. Three grassland field margin treatments (fencing off the existing vegetation "fenced"; fencing with rotavation and natural regeneration "rotavated" and; fencing with rotavation and seeding "seeded") were compared to a grazed control in the adjacent intensively managed pasture. Invertebrates were sampled using emergence traps to investigate species breeding and overwintering within the margins. Using a manipulation experiment, we tested whether the removal of grazing pressure and nutrient inputs would increase the abundance and richness of breeding invertebrates within grassland field margins. We also tested whether field margin establishment treatments, with their different vegetation communities, would change the abundance and richness of breeding invertebrates in the field margins. Exclusion of grazing and nutrient inputs led to increased abundance and richness in nearly all invertebrate groups that we sampled. However, there were more complex effects of field margin establishment treatment on the abundance and richness of invertebrate taxa. Each of the three establishment treatments supported a distinct invertebrate community. The removal of grazing from grassland field margins provided a greater range of overwintering/breeding habitat for invertebrates. We demonstrate the capacity of field margin establishment to increase the abundance and richness in nearly all invertebrate groups in study plots that were located on previously more depauperate areas of intensively managed grassland. These results from grassland field margins provide evidence to support practical actions that can inform Greening (Pillar 1) and agri‐environment measures (Pillar 2) of the Common Agricultural Policy (CAP). Before implementing specific management regimes, the conservation aims of agri‐environment measures should be clarified by defining the target species or taxonomic groups. Abstract : We used a manipulation field experiment to test whether exclusion of grazing pressure (by fencing), natural regeneration by rotavation or seeding with a wildflower mixture would increase the abundance and richness of breeding invertebrates in grassland field margins. Exclusion of grazing led to an increased abundance and richness in nearly all invertebrate groups that we sampled. However, differences between fencing, natural regeneration, and seeding treatments were different depending on the invertebrate taxa examined.